Financing the General Budget Deficit in the Arab Gulf Oil States and the Possibility of Benefiting from it in Iraq: The Kingdom of Saudi Arabia as a Model - Baroud, Maryam Najeh Abdul Amir; Shuaibeth, Sondos Jassim (جامعة القادسية - كلية الادارة والاقتصاد, 2022)
المملكة العربية السعودية أحد دول الخليج العربي الغنية بالنفط، وهي من الدول التي تشترك في خصائصها مع جميع دول الخليج ومنها العراق، وأهمها أنها دولة عربية ريعية. مع اقتصاد يعتمد بشكل كبير على الموارد الريعية (النفط) في إدارة أنشطتها الاقتصادية وفي تمويل ميزانياتها العامة بالموارد المالية. غالبا ما يكون اقتصاد هذه البلدان ضعيفا ويعتمد على التبادلات التجارية، ويؤدي إلى مجتمع استهلاكي يسيطر عليها قطاع الاستيراد العشوائي. بالنسبة لهذه الدول، وبالطبع، تعاني هذه الدول من أزمات اقتصادية تحدث من حين لآخر وتنعكس في ميزانيتها العامة، نتيجة ارتباط تجارتها الخارجية بالعالم بتصدير مورد واحد فقط، وهو هو المصدر الوحيد للإيرادات العامة بالنسبة لهم. لذلك سعت المملكة العربية السعودية إلى معالجة مشكلة عجز الموازنة. وقد نجحت ونجحت في ذلك بشكل كبير، ونظرا لتشابه الاقتصاد العراقي مع الاقتصاد السعودي الكبير، فقد تم اتخاذه كنموذج يمكن دراسته والاستفادة منه لمعالجة العجز الذي يحدث في الموازنة العامة للعراق. في بعض السنوات. The Kingdom of Saudi Arabia is one of the oil-rich Arab Gulf countries, and it is one of the countries that have common characteristics with all the Gulf countries, including Iraq, and the most important of them is that it is an Arab rentier country with an economy that depends heavily on rentier (oil) resources in the conduct of its economic activities and in financing its public budgets with financial resources The economy of these countries is often soft and dependent on trade exchanges, and it results in a consumer society that is dominated by the random import sector. For these countries, and of course, these countries suffer from economic crises that occur from time to time and that are reflected in their general budget, as a result of their foreign trade being linked with the world with the export of only one resource, which is the only source of public revenues for them. Therefore, the Kingdom of Saudi Arabia sought to address the problem of the budget deficit. It has, and has succeeded in this greatly, and given the similarity of the Iraqi economy with the Saudi economy Large, it has been taken as a model that can be studied and benefited from to address the deficit that occurs in the general budget of Iraq in some years.
Keywords: الاقتصاد العراقي -- الاقتصاد السعودي -- الأزمات الاقتصادية -- عجز الموازنة -- الموارد النفطية -- التبادلات العراقية